ONLINE-BASED EVALUATION MODEL ON TEACHER STUDENTS: A CASE STUDY IN THE TIME COVID-19 PANDEMIC (MODEL EVALUASI BERBASIS DARING PADA PERKULIAHAN MAHASISWA KEGURUAN: STUDI KASUS DI MASA PANDEMI COVID-19) - Trisna Helda; Yulia Pebriani; Refa Lina Tiawati; Rina Sartika; Upit Yulianti (Jurnal Gramatika, 2022)
The implementation of distance education during the Covid-19 pandemic caused various problems, especially in relation to the evaluation (assessment) process in student lectures at the Indonesian Language and Literature Study Program STKIP PGRI West Sumatra. Therefore it is necessary to have an alternative evaluation model that supports the good and effective distance lecture process, both for lecturers and students. This paper provides an overview of an evaluation model that can be used as a reference for lecturers in evaluating distance student learning outcomes during the Covid-19 pandemic that is hitting Indonesia. This research method is qualitative based on descriptive study, including the type of research library research. Researchers obtained data from interviews with student lecturers and parents and literature studies from various literature books, journals, scientific papers, and also other documents that assess the evaluation of distance lectures. The results of this study found several things, namely: (1) types of evaluation difficulties during lectures during the Covid-19 period, (2) lecture evaluation models during the Covid-19 pandemic, and (3) various obstacles faced in implementing evaluation during lectures during the Covid-19 pandemic.